2010
DOI: 10.1002/jsfa.4184
|View full text |Cite
|
Sign up to set email alerts
|

Changes in volatile compounds upon aging and drying in oolong tea production

Abstract: Characteristic aroma nitrogen-containing compounds, including N-ethylsuccinimide, 2-acetylpyrrole, 2-formylpyrrole and 3-pyridinol, were consistently found in the examined old oolong teas. These compounds might be regarded as typical constituents at least for a certain kind of old oolong tea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…Comparing the results of other studies, a total of 36 compounds mare tentatively identified using agreement with their mass spectra in fresh Oolong tea (Kuo et al, 2011), more than 70 volatile flavor compouds are detected in Dongding Oolong (Wang et al, 2008); 52 compounds are identified from the brewed extract and 100 compounds from the SDE of Huang Chin Kuei, respectively. 49 compounds were identified from the brewed extract of Chan Pin Oolong (Kawakami et al, 1995); and Wang has reported that nerolidol, indole, benzene acetaldehyde, linalool, linalool oxides, hexanal, benzyl nitrile, (E)-geraniol and 1-penten-3ol are the prevailing volatile compounds detected in most of Oolong tea samples.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Comparing the results of other studies, a total of 36 compounds mare tentatively identified using agreement with their mass spectra in fresh Oolong tea (Kuo et al, 2011), more than 70 volatile flavor compouds are detected in Dongding Oolong (Wang et al, 2008); 52 compounds are identified from the brewed extract and 100 compounds from the SDE of Huang Chin Kuei, respectively. 49 compounds were identified from the brewed extract of Chan Pin Oolong (Kawakami et al, 1995); and Wang has reported that nerolidol, indole, benzene acetaldehyde, linalool, linalool oxides, hexanal, benzyl nitrile, (E)-geraniol and 1-penten-3ol are the prevailing volatile compounds detected in most of Oolong tea samples.…”
Section: Resultssupporting
confidence: 61%
“…Identification and quantification of volatile composition in Rock tea infusion The aroma constituents of various tea products are interesting research topics with potential commercial values and have been continually investigated. The first scientific studies were performed more than 70 years ago (Yamanishi and Kobayashi, 1999), leading to the identification of linalool, geraniol and (Z)-3-hexenol in the volatile fractions of the tea leaf and beverage (Kuo et al, 2011). In our study, the GC/MS min to 240℃, and hold for 5 min.…”
Section: Resultsmentioning
confidence: 94%
“…The variables that explained maximum variance in the data had high contributions and were considered important in discriminating samples between oolong tea and other types of teas. Benzylalcohol (V13), linalool oxides (V19, V20, V25, and V26), safranal (V30), indole (V39), β -ionone (V61), and hexadecanoic acid methyl ester (V87), which contributed to the fruity and flower-like aroma, had high positive values in oolong tea and were thought to enhance their aroma flavor (Kuo et al 2011 ). These volatile compounds in oolong tea reached their highest levels during semi-fermentation (Wang et al 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…Actually, the term ‘tea fermentation’ in this context refers to natural browning reactions induced by oxidative enzymes in the cells of tea leaves (Kuo et al, 2011). The effect of tea fermentation on antioxidant properties of IOSC are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%